Understanding Hadiths on Trustworthiness and Fulfilling Promises in the Kutub Al-Tis'ah - Syahrul Gunawan; Budiman Muhammad Nur (STAI Serdang Lubuk Pakam, 2026)
This study examines hadiths concerning trustworthiness (amanah) and fulfilling promises (wafa’ bil-‘ahd) within the Kutub al-Tis‘ah as fundamental ethical values in Islam. These values play a crucial role in shaping individual character, strengthening social trust, and reflecting the quality of faith. The study aims to analyze the meanings, thematic dimensions, and contemporary relevance of hadiths related to trustworthiness and promise-keeping. A qualitative approach was employed using library research methods, drawing on primary data from the Kutub al-Tis‘ah and supported by relevant scholarly literature. Data were analyzed through thematic (maudhu‘i) hadith analysis, including takhrij, textual interpretation, and contextual examination. The findings reveal that trustworthiness and fulfilling promises are central indicators of Islamic moral integrity and authentic faith, while betrayal of trust and breaking promises are portrayed as characteristics of hypocrisy. The study concludes that these prophetic teachings remain highly relevant for contemporary life, particularly in education, leadership, social relations, and professional ethics, contributing to the development of responsible, honest, and trustworthy individuals.